STUDI BENTUK, MOTIF, TEKNIK DAN WARNA TENUN SONGKET KOTA LUBUKLINGGAU SUMATERA SELATAN - Maria Ulfa, Drs. Erwin, M.Sn., Dra. Zubaidah, M.Pd. (Serupa The Journal of Art Education, 2018)
The purpose of this research was to know the shape of the product, the range of motifs, techniques of making and color woven songket Lubuklinggau. The methods used to collect the data was the methods of observation, documentation and interviews. The result of the research shows five types of products including: Lubuklinggau songket Sarong, Shawl, fabric aside, the Tanjak and wall hangings. Songket Lubuklinggau has six motif was already patented, namely: 1. Motif Rope Duren Aer, 2. Motif Duren Limar pretty sweet, 3. Motive Duren Dodot Duren Motif, 4. Cempuk 5. Motive Duren cages and 6. Serial Duren Motif, technique used in making technique: with a songket gouged, the colors found in the weaving songket varies, was Gold , Red, Dark Green, Dark Blue, Light Blue, Purple, Black and Limar.Key Words: Songket, Lubuklinggau